Effects of dried cassava pulp as a source of energy on growth performance and carcass quality in fattening beef cattle - Laorodphan,N. (Chiang Mai University, 2015)
This study was conducted to determine effects of feeding dried cassava pulp (DCP) as a main source of energy on growth performance, carcass composition and economic return of feedlot cattle. Twenty mature Charolais crossbred steers at an average age of 3 years were used in this study. The feedlot cattle were randomly divided into 4 groups of 5 animals and were randomly allotted to receive one of four dietary treatments according to a Completely Randomized Design (CRD). The animals in control (CTRL) and dietary treatment were fed with concentrate at 1 percentage of body weight and supplemented with rice straw to the animals ad libitum. The other 3 treatments were fed with concentrate in which corn and rice bran was replaced by dried cassava pulp (DCP) at 50, 75 and 100% by weight. The results indicated that feedlot performances (ADG, FCR and feed efficiency) were not significantly different. Additionally, carcass compositions (carcass length, carcass weight, dressing percentage, lean percentage, bone percentage, fat percentage and fat thickness) and carcass quality (chemical composition, water holding capacity, marbling score and shear force) were not significantly different. However, meat color values of b* value of control diet and DCP50 were higher than DCP100 (P<0.05). Note that the total feed cost of control group was higher then DCP50, DCP75 and DCP100 (P<0.05). The results from this study suggested that DCP can be used as an energy source for feedlot cattle without any impact on growth performances, carcass compositions and carcass quality.